31.9k views
4 votes
4(3-5p) = -5(3p – 4) step by step please

1 Answer

4 votes

Answer:

-1.6.

Explanation:

So we have the equation:


4(3-5p)=-5(3p-4)

Distribute both sides:


12-20p=-15p+20

Add 15p to both sides. The right side will cancel:


12-5p=20

Subtract 12 from both sides:


-5p=8

Divide both sides by -5:


p=-(8)/(5)

Or -1.6.

And we're done!

User Henri Kerola
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.